2018
DOI: 10.1177/1403494818771444
|View full text |Cite
|
Sign up to set email alerts
|

Development and predictors of psychological outcomes following the 2008 earthquake in Iceland: a longitudinal cohort study

Abstract: Findings indicate a reduction in anxiety symptoms between 2 and 12 months post-disaster, with PTSD and depression symptoms remaining fairly constant across time. No trends in symptomology were observed over time. The results highlight the need for continued monitoring of those affected by disasters and the identification of subgroups at risk in the aftermath of natural disasters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Our analyses include three groups of participants that were identi ed by local proximity as well as help seeking behavior post-re. Previous research suggests an association of mental health outcomes after disasters, and the degree of exposure as measured in distance to the disaster, degree of household damage or physical injury (22,27,28). Here, in the context of res, we con rmed that our cohort were directly exposed (i.e., to whom the re happened to), indirectly exposed (i.e., who have witnessed the re) and not exposed (i.e., who have learned about the re) as per their self-reported re exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses include three groups of participants that were identi ed by local proximity as well as help seeking behavior post-re. Previous research suggests an association of mental health outcomes after disasters, and the degree of exposure as measured in distance to the disaster, degree of household damage or physical injury (22,27,28). Here, in the context of res, we con rmed that our cohort were directly exposed (i.e., to whom the re happened to), indirectly exposed (i.e., who have witnessed the re) and not exposed (i.e., who have learned about the re) as per their self-reported re exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests that an adverse impact of environmental disasters is dependent on the degree of disaster exposure. In those studies, degree of exposure was de ned objectively (e.g., as geographical distance of residence from the epicenter of the disaster) (27,28) or subjectively (e.g., as degree of household damage) (27). It has also been shown that PTSD symptoms occur in relation to re exposure particularly in highly exposed individuals, who experienced loss of residency or injuries (22).…”
Section: Introductionmentioning
confidence: 99%
“…If the purpose of the tool's use is to build knowledge to develop programs for disaster mitigation, then inconsistent measures and cutoffs would hinder this goal [173,174]. Those who work in humanitarian response and research and use these tools must consult the • Availability of multiple languages [87] • Not culture-specific [87] • Tool is in English, not Tibetan language [91] • May not be extrapolated to other populations [92] • Not validated in Haitian contexts and Western tools may not be appropriate [93] • Self-report [94] • Tibetan refugees in North India [91] • Chinese elderly 2013 Ya'an earthquake survivors [92] • 2010 earthquake-exposed Haitians in Florida [87,93] • 2008 Iceland earthquake survivors [94] Language(s):…”
Section: Pss-sr N/a N/a Ptcimentioning
confidence: 99%
“…• Can be administered online, convenient, accessible [95] • Widely used [96] • Self-report and subjective [94][95][96][97] • Valid Nepali language version does not exist [97] • 2008 Iceland earthquake survivors [94] • Pet owners who survived Hurricane Katrina [95] • Parents of internally displaced children in Georgia [96] • Nepalese 2015 earthquake survivors in Phulpingdanda village [97] Language(s):…”
Section: Pss-sr N/a N/a Ptcimentioning
confidence: 99%
See 1 more Smart Citation